Pengaruh Brand Image terhadap Repurchase Intention dengan Digital Marketing sebagai Variabel Moderasi pada Pengguna Sepatu Nike di Kota Semarang - Muhammad Safi’I; Heru Sulistyo (ARZUSIN, 2025)
The increasingly intense competition in the sports shoe industry requires companies not only to rely on product quality but also to build a strong brand image and optimize digital marketing strategies to sustain consumer loyalty, particularly among athletes. This study aimed to analyze the effect of brand image on repurchase intention and to examine the role of digital marketing as a moderating variable among athlete users of Nike shoes in Semarang City. A quantitative approach with an explanatory research design was employed. Data were collected through an online questionnaire administered to 120 respondents and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that brand image does not have a significant direct effect on repurchase intention; however, digital marketing was found to moderate and strengthen the influence of brand image on repurchase intention. These findings indicate that brand image alone is not sufficient to drive repeat purchases without the support of effective digital marketing strategies. The implications of this study underscore the importance of optimizing digital marketing as a means of communication, interaction, and reinforcement of brand perceptions to enhance consumers’ repurchase decisions, while also providing practical guidance for companies in designing digital-based marketing strategies to increase customer loyalty.